KADAR INTERLEUKIN 10 (IL-10) MALARIA DAN ANEMIA - I Nyoman Wande; Endang Retnowati; Juli Soemarsono (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2011)
Anaemia is an important complication of malaria, and its pathogenesis is not well understood. High level of the Th2 cytokine (such as IL-10), which counteract the Th1 cytokine, might prevent the development of severe malarial anaemia. The purpose of this study was to know the comparation between the plasma level of IL-10 in malaria patients with anaemia and without anaemia. The plasma level of IL-10 was examined in 16 malaria patients with anaemia and 16 malaria caused by P. falciparum patients without anaemia samplestaken from patients at the primary health centres in West Lombok and Centre Lombok during March until July 2008. The samples were measured using ELISA. The concentration of haemoglobin (Hb) was measured using hematological analyzer. The anaemia concentration of Hb is <11 g/dL. The results were analyzed using two (2) sample t test with SPSS ver.13.The plasma level of IL-10 in malaria patients caused by P. falciparum with anaemia was 8.81(3.04) [mean(SD)] pg/mL where as the plasma level of IL-10 in malaria patients without anaemia was 47.99(25.26) pg/mL. The mean of IL-10 level in malaria falciparum patients with anaemia was significantly lower than that of malaria patients caused by P. falciparum without anaemia (p=0.000).